Yemen Economic Monitoring Note, Fall 2012 - World Bank (World Bank, Washington, DC, 2017)
After almost a year of political, economic, and security upheaval, Yemen has now embarked on a new political path based on an agreement brokered by the Gulf Cooperation Council (GCC) and overseen by the United Nations, or UN and the international community. The agreement was signed on November 23, 2011, after former President Saleh, the ruling party (GPC), and the opposition parties agreed to a political transition, dialogue, and political reforms. A transitional government of national unity was formed and confirmed by the Parliament in early December 2011. The transition President Hadi was elected on February, 21 2012, for the period spanning to the planned next general elections in the first half of 2014. In an environment of political tensions, the President made progress in reforming the security institutional set-up, in reducing the influence of Al-Qaeda forces, and in preparing for a national dialogue.